Genome sequence and comparative analysis of fungal antagonistic strain Bacillus velezensis LJBV19 - Wang, Bo; Yang, Bohan; Peng, Hang; Lu, Jiang; Fu, Peining (Folia microbiologica, 2023)
Bacillus species as fungal antagonistic agents have been widely used in the agriculture and considered as safe products for the management of plant pathogens. In this study, we reported the whole genome sequence of strain LJBV19 isolated from grapevine rhizosphere soil. Strain LJBV19 was identified as Bacillus velezensis through morphological, physicochemical, molecular analysis and genome comparison. Bacillus velezensis LJBV19 had a significant inhibitory effect on the growth of Magnaporthe oryzae with an inhibition ratio up to 75.55% and showed broad spectrum of activity against fungal phytopathogens. The 3,973,013-bp circular chromosome with an average GC content of 46.5% consisted of 3993 open reading frames (ORFs), and 3308 ORFs were classified into 19 cluster of orthologous groups of proteins (COG) categories. Genes related to cell wall degrading enzymes were predicted by Carbohydrate-Active enZYmes (CAZy) database and validated at the metabolic level, producing 0.53 ± 0.00 U/mL cellulose, 0.14 ± 0.01 U/mL chitinase, and 0.11 ± 0.01 U/mL chitosanase. Genome comparison confirmed the taxonomic position of LJBV19, conserved genomic structure, and genetic homogeneity. Moreover, 13 gene clusters for biosynthesis of secondary metabolites in LJBV19 genome were identified and two unique clusters (clusters 2 and 12) shown to direct an unknown compound were only present in strain LJBV19. In general, our results will provide insights into the antifungal mechanisms of Bacillus velezensis LJBV19 and further application of the strain.
Keywords: Comparative genomics; Secondary metabolites; genomika; Genome, Bacterial; antifungální látky; Antifungal Agents; Bacillus velezensis; Genome sequencing; genom bakteriální; Fungal antagonistic; Bacillus; Genomics